2009
DOI: 10.1021/la9016799
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Red Blood Cell Recognition toward Anti-A Antibody by Means of Polyelectrolyte Layer-by-Layer Assembly in a Two-Dimensional Model System

Abstract: Silencing the antigenic response of red blood cells (RBCs) is a prerequisite toward the development of universal blood transfusion. Using a two-dimensional (2D) model whereby nonfixed RBCs are adsorbed on a human fibronectin (HFN)-coated surface, we demonstrate that the layer-by-layer (LbL) assembly technique of biocompatible polyelectrolytes can be employed to achieve the immunocamouflage of RBCs against the Anti-A antibody while maintaining the integrity and viability of the cells. The multilayered film cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…22, 23 The biocompatibility, ready availability and low cost of charged polysaccharides have made them attractive choices for a range of applications, including drug delivery vehicles based on lipid-polyelectrolyte particles, biocompatible surfaces for controlling cell growth and tissue biomimetics. [23][24][25][26][27][28] We have examined the suitability of PEM films constructed from alternating layers of chitosan (CHI) and hyaluronic acid (HA) as polymer cushions for supported lipid bilayers.…”
Section: -21mentioning
confidence: 99%
“…22, 23 The biocompatibility, ready availability and low cost of charged polysaccharides have made them attractive choices for a range of applications, including drug delivery vehicles based on lipid-polyelectrolyte particles, biocompatible surfaces for controlling cell growth and tissue biomimetics. [23][24][25][26][27][28] We have examined the suitability of PEM films constructed from alternating layers of chitosan (CHI) and hyaluronic acid (HA) as polymer cushions for supported lipid bilayers.…”
Section: -21mentioning
confidence: 99%
“…Recent work with cast films composed of water‐soluble phosphorylcholine‐modified chitosan (Pc‐CHI) has indicated significantly improved bone marrow cellular adhesion properties in comparison to unmodified CHI 19. Meanwhile, initial studies of LbL films composed of Pc‐CHI and HA have demonstrated biocompatibility 20, 21. The more commercially available glycol‐modified chitosan (Glyc‐CHI) also exhibits significantly improved water solubility and biocompatibility, features that have led to its wide deployment in drug delivery systems, as well as in gene therapy and tissue engineering applications 22–25.…”
Section: Introductionmentioning
confidence: 99%
“…Tabrizian and colleagues [64,97] have recently taken a different polymer film engineering approach to generating a universal RBC. Instead relying on a single polymer layer to form a steric barrier between RBC surface antigens and antibodies, they instead assembled a PEM thin film on the surface of RBCs.…”
Section: Molecular Camouflage and Nano-encapsulationmentioning
confidence: 99%